Face Masks and Prevention of Respiratory Viral Infections: An Overview - Chiu-Sen Wang (Aerosol and Air Quality Research)
Abstract Airborne transmission of respiratory viruses consists of three sequential steps: (1) release of respiratory fluids in the form of droplets from the nose and mouth of an infected person, (2) transport of the droplets through air, and (3) entry of the droplets into the nose and mouth of an uninfected individual. Talking, coughing, and sneezing emit droplets across a spectrum of sizes. The water in exhaled droplets begins to evaporate in air and, as a result, the droplets are reduced in size shortly after being emitted. Face masks are effective for capturing droplets just released from the nose and mouth. Studies indicate that more than 50% of community transmission of SARS-CoV-2 is from asymptomatic and pre-symptomatic cases. Use of face masks by the public can effectively reduce the chance of infected individuals unknowingly spreading the virus. In addition to being an effective device for source control, face masks can protect the wearers from inhaling virus-laden droplets. Cloth masks and disposable masks provide reasonable protection for the public, while surgical masks and N95 respirators give higher levels of protection as needed in healthcare settings. Made with varied materials, these masks have different structural characteristics. The collection efficiency of a face mask depends on droplet size, face velocity, and the structural characteristics of the mask. For a given mask, capturing droplets is more effective during exhalation than during inhalation. Pressure drop across the mask should be taken into consideration when selecting a face mask. The best face mask is the one that gives the highest collection efficiency with the least pressure drop. For an effective protection, a mask should fit the face properly. While face masks have proven adequate in reducing airborne transmission of SARS-CoV-2 infections, continuous improvement is needed to better prepare for future respiratory viral threats.